Argentina : Detailed Assessment of Observance of Principles for Insurance Supervision. (IMF Staff Country Reports; Country Report ;, 2012)
Argentina's insurance market is fragmented, and competition has increased in recent years. Currently, excessive premium discounting by insurance companies is creating risks that insurance companies may be under-reserved and may not be able to meet future liabilities. The evolution of liability insurance is positive but will require developing specific expertise. In line with developments around the world, the adoption of a risk-based supervisory approach is essential to properly monitor a rapidly evolving market. To successfully address these challenges, additional resources as well as operational independence is required.